Older men’s social integration after prison - Wyse, Jessica (International journal of offender therapy and comparative criminology, 2018)
This study explores the social integration processes older men experience following prison release. Semi-structured in-depth interviews and brief surveys were conducted with 20 men, 50 years of age and older, recently released from prison in a large, Eastern U.S. city. A follow-up interview was conducted with each participant. Conventional content analysis was used to analyze these data. Results show that while men are able to connect with and rely upon some family members and establish basic public benefits, older men’s release experience is nonetheless marked by pervasive disconnection from key desired social relationships and roles. Policies and programs designed to facilitate older men’s social integration are discussed.